Evaluation of Scrum-based Software Development Project Management Maturity Level at Bank Z - Emyria Natalia (Al-Makki Publisher, 2025)
In the era of growing connectivity and the digital world, the growth of information technology requires organizations to adapt more efficient and effective software development methods. This research aims to measure the maturity level of Scrum-based software development project management at Bank Z, which has been implementing Agile approaches since 2023. With the challenges faced in timely project completion, this research explores the obstacles faced by Scrum teams and provides improvement recommendations to increase the efficiency and effectiveness of software development. The research methodology used includes quantitative and qualitative approaches, with data collection through questionnaires and interviews. The results show that the maturity level of the Scrum process at Bank Z is at level 2 (Managed), with some areas such as backlog management and Scrum meetings being well implemented. However, there is a need to improve transparency and collaboration between teams. Recommendations include increased training and consistent implementation of Scrum practices to achieve a higher level of maturity.